2021
DOI: 10.1515/mt-2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of thermoplastic liner materials with regard to mechanical and permeation barrier properties before and after cyclic thermal aging

Abstract: Lightweight pressure vessels of type IV for hydrogen storage consist of a thermoplastic inner liner, commonly from polyethylene or polyamide. The liner is the permeation barrier against the compressed gas and must prevent the formation of cracks, also after temperature changes, for example after refueling processes. In the present work high-density polyethylene, cross-linked polyethylene, polyamide 6 and polyamide 12 were characterized by tensile tests, single notch impact tests and permeations measurements be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Some studies have shown that polyethylene has good gas barrier properties and can be used as a plastic liner for hydrogen storage cylinders [12]. However, compared with polyethylene, polyamide is more suitable as a plastic lining for hydrogen storage bottles due to its strong molecular polarity and low gas permeability, and many scholars have conducted research in this area [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that polyethylene has good gas barrier properties and can be used as a plastic liner for hydrogen storage cylinders [12]. However, compared with polyethylene, polyamide is more suitable as a plastic lining for hydrogen storage bottles due to its strong molecular polarity and low gas permeability, and many scholars have conducted research in this area [13,14].…”
Section: Introductionmentioning
confidence: 99%